Batch production of uniform graphene films via controlling gas-phase dynamics in confined space. (18th December 2020) - Zhang, Yongna; Huang, Deping; Duan, Yinwu; Chen, Hui; Tang, Linlong; Shi, Mingquan; Li, Zhancheng; Shi, Haofei
Abstract: Batch production of continuous and uniform graphene films is critical for the application of graphene. Chemical vapor deposition (CVD) has shown great promise for mass producing high-quality graphene films. However, the critical factors affected the uniformity of graphene films during the batch production need to be further studied. Herein, we propose a method for batch production of uniform graphene films by controlling the gaseous carbon source to be uniformly distributed near the substrate surface. By designing the growth space of graphene into a rectangular channel structure, we adjusted the velocity of feedstock gas flow to be uniformly distributed in the channel, which is critical for uniform graphene growth. The monolayer graphene film grown inside the rectangular channel structure shows high uniformity with average sheet resistance of 345 Ω sq −1 without doping. The experimental and simulation results show that the placement of the substrates during batch growth of graphene films will greatly affect the distribution of gas-phase dynamics near the substrate surface and the growth process of graphene. Uniform graphene films with large-scale can be prepared in batches by adjusting the distribution of gas-phase dynamics.